Hubungan Antara Persepsi Keharmonisan Keluarga dengan Kenakalan Remaja - Ma'rifatun Hasanah, Indah, Dra. Wiwien Dinar Prastiti, M.Si (2015)
Juvenile delinquency from year to year is increasingly better along with the progress the days of .Supposed to be when perception harmonious family building high the juvenile delinquency low .In fact juvenile delinquency the meninggkat , how perception harmonious family building .This study aims to to look back on perception harmonious family building had a role on juvenile delinquency .Researchers chose quantitative methods to achieve the purpose of this research . The subject of study used in this research was a student of class x SMK Batur Jaya 1 Ceper Klaten batur consisting of three classes : x tpm class b , tpl x b , and x tkr d who is a total of 87 people .Engineering the sample used in this research is clusters of random sampling .This study using a scale perception harmonious family building and juvenile delinquency that are analyzed with employing correlation product moment pearson . Based on the analysis of using a technique that has been done with correlation product moment pearson then obtained the results of the value of a correlation coefficient ( r ) as much as -0,641 with p value = 0,000 & it; 0.01 that means that there are very significant negative relationship between perception harmonious family building with juvenile delinquency .Based on the analysis of variable known perception harmonious family building have empirical average ( RE ) as much as 65.98 and hypothetic average ( RH ) as much as 52.5 which means perception harmonious family building a subject of study considered to be high .Variable juvenile delinquency have empirical average ( RE ) as much as 25,44 and hypothetic average ( RH ) as much as 42,5 which means juvenile delinquency on the subject of study is considered to be very low .Effective contributions perception harmonious family building against juvenile delinquency reached 41 % .This indicates variable variable perception harmonious family building affect juvenile delinquency . Keywords: juvenile delinquency, family harmony, perception